Five-nuclear phthalocyanine complex bearing terpyridine zinc complex: Synthesis, and photophysicochemical studies - Sen, Pinar; Yildiz, S. Zeki; Atmaca, Goknur Yasa; Erdogmus, Ali (WORLD SCI PUBL CO INC, 2018)
The context of this study is based on the synthesis of tetrakis{4-(2-([2,2': 6', 2 ''-terpyridine]Zn(II)-4'-yl(methyl) amino) ethoxy)} phthalocyaninato zinc (II) (3) bearing four terpyridine-Zn(II) complexes that are directly linked through oxygen bridges to the macrocyclic core in order to create new supramolecular assemblies. The target phthalocyanine (3) was obtained by cyclotetramerization reaction of terpyridine-Zn (II) complex substituted phthalonitrile (2). All novel compounds synthesized in this study were fully characterized by general spectroscopic techniques such as FT-IR, UV-vis, and H-1-NMR, C-13-NMR, elemental analysis and mass spectroscopy. Spectral, photophysical (fluorescence quantum yields and lifetimes) and photochemical (singlet oxygen production and photodegradation under light irradiation) properties of newly synthesized phthalonitrile (2) and its phthalocyanine derivative (3) as five nuclear phthalocyanine were investigated in DMSO solutions.
Keywords: metallophthalocyanine; terpyridine complex; fluorescence property; singlet oxygen; photodegradation; PHOTOCHEMICAL PROPERTIES; INDIUM(III) PHTHALOCYANINES; PHOTODYNAMIC THERAPY; DERIVATIVES; ELECTROCHEMISTRY; PHOTOSENSITIZER; PORPHYRIN; CATALYSTS; PHENOXY; LIGANDS; Chemistry